2002
DOI: 10.1046/j.1468-1293.2002.00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Body composition changes in protease inhibitor‐naive HIV‐infected patients treated with two nucleoside reverse transcriptase inhibitors

Abstract: Dual NRTI therapy contributes to fat loss and reduction of bone mineral content in otherwise healthy, clinically stable, PI-naive HIV-infected adults. Compared with patients on ZDV + ddI, patients on ZDV + 3TC had a more prominent fat loss in all body regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 19 publications
0
20
0
1
Order By: Relevance
“…Previous reports suggest that boosted PI is associated with lower bone mineral content and TB BMD [6]. Others have found adverse bone effects associated with regimens containing lamivudine and zidovudine [25, 26]. Indinavir is known to increase osteoclast activity [27].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports suggest that boosted PI is associated with lower bone mineral content and TB BMD [6]. Others have found adverse bone effects associated with regimens containing lamivudine and zidovudine [25, 26]. Indinavir is known to increase osteoclast activity [27].…”
Section: Discussionmentioning
confidence: 99%
“…A low nadir CD4 cell count has been shown to be an independent risk factor for both reduced BMD and increased fracture incidence after adjustment for BMI (34). Time from date of diagnosis and prolonged exposure to unsuppressed HIV was also found to be an independent risk factor for loss of BMD in three studies (33).…”
Section: Does Hiv Cause Low Bone Mineral Density?mentioning
confidence: 99%
“…Similarly, Carr et al reported that 3% of 44 HIV-infected patients receiving NRTIs developed osteoporosis and 22% developed osteopenia [39], while in a study examining HIV-1 infected men Mallon et al determined a reduction in BMD beginning at 48 weeks post initiation of treatment [40]. Tsekes et al determined BMD and whole body fat by dual-energy X ray absorbance (DEXA) of HIV-infected patients receiving Zidovudine (AZT) and other NRTIs and found significant decreases in both body fat and BMD [41].…”
Section: Hiv-1 Associated Bone Abnormalitiesmentioning
confidence: 99%